Design and Performance Research of a Wearable Airbag for the Human Body - Xuerong Zhang; Zhixiang Xue; Wenqiong Tu (Applied Sciences, 2023)
In this paper, an integrated wearable airbag is proposed to protect the vulnerable pedestrian during a vehicle–pedestrian collision accident. To evaluate the protection performance of this newly proposed integrated wearable airbag, the airbag inflator finite element model is first verified via an inflator tank test, and the simulated results agree very well with the test. Next, the finite element model of the vehicle–pedestrian model is established, including a simplified vehicle model and a biomechanical HBM with the integrated wearable airbag. The numerical results show the newly proposed wearable airbag can effectively protect the pedestrian by significantly reducing injuries to the head and chest. Since head injury is the most important injury type, a complete set of injury indexes is adopted to evaluate severity of head injury, including HIC15, 3 ms resultant acceleration, and intracranial pressure. To further improve the protection performance of the airbag on the HBM’s head, a parametric study is conducted towards two design parameters of the wearable airbag: inflator gas mass and pulling strap length. The parametric investigation shows 26 g gas and a 20 mm pulling strap can provide the best protection for the HBM’s head.